GIS-material for the archaeological project: An archaeological line project in western Östergötland - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archeological report:
The results of the archaeological investigations and preliminary investigations presented in this report is part of a work in progress along the railway line Mjölby - Hallsberg. The investigated section are running between Mjölby and Motala in the western part of Östergötland and was early identified as one of the province's major central areas. The survey found many relics that have been dated from the Mesolithic period , 6000 - 8000 BC, up to early modern period. Among other things, a new and unique mesolitisk residence was found at the Motala Ström beach. Skänninge is another location where new information has come to light. Remains of extensive engineering activities were found outside the central medieval city area. Along the railway tracks several sites has shown on settlements from the Bronze Age and early Iron Age, periods which we previously had little knowledge about in this part of Östergötland.

Purpose:

The information in the purpose is translated from the archeological report:
The reason for the investigations is the Swedish Rail Administration's (Banverket) planned double track between Motala and Mjölby.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Resultaten från de arkeologiska utredningar och förundersökningar som redovisas i denna rapport är en del i ett pågående arbete längs med järnvägssträckan Mjölby - Hallsberg. Den delsträcka som nu är aktuell löper mellan Mjölby och Motala i den västra delen av Östergötland som tidigt har pekats ut som ett av landskapets mer betydande centralområden.
Vid undersökningarna påträffades en mängd fornlämningar som tidsmässigt omfattar perioderna från mesolitikum, 6000 - 8000 år f Kr, till och med medeltid/tidig modern tid. Bland annat en nyupptäckt och för Östergötland unik mesolitisk bosättning vid Motala Ströms strand. Skänninge är ytterligare en plats där helt ny information har kommit i dagen. Där påträffades lämningar efter omfattande verkstadsaktiviteter utanför det centrala medeltida stadsområdet. Längs med bansträckningen har ett flertal platser visat på bosättning från bronsålder och äldre järnålder, perioder som vi tidigare haft liten kännedom om i denna del av Östergötland.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Anledningen till undersökningarna är Banverkets planerade dubbelspår mellan Motala och Mjölby.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Ett arkeologiskt linjeprojekt i västra Östergötland
Keywords: stone age; stenålder; Bronze Age; bronsålder; Iron Age; järnålder; Middle Ages; medeltid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi